2009
DOI: 10.1590/s0102-311x2009000900016
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive discontinuation and non-use in Santarém, Brazilian Amazon

Abstract: In this paper we discuss the causes of non-adherence to reversible contraceptives, especially hormonal methods, among women in rural Santarém in the Brazilian Amazon. The analysis is based on questionnaires with 398 women and visits to health centers. We consider the motives reported by women who: never used contraception; used some method in the past; and who at the time of the survey were using a different method from the ones they used in the past. The results indicate a rejection of hormonal contraception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
(22 reference statements)
0
12
0
3
Order By: Relevance
“…Studies carried out in both developed and developing countries have also shown that the experience of side-effects as well as the fear of side-effects are major reasons for discontinuation. [7][8][9][10] It appeared that fear of side-effects was a unique barrier across different countries and cultures. Minor side-effects such as breast tenderness, fluid retention, nausea, and vomiting were transient and usually subsided after one to two cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in both developed and developing countries have also shown that the experience of side-effects as well as the fear of side-effects are major reasons for discontinuation. [7][8][9][10] It appeared that fear of side-effects was a unique barrier across different countries and cultures. Minor side-effects such as breast tenderness, fluid retention, nausea, and vomiting were transient and usually subsided after one to two cycles.…”
Section: Discussionmentioning
confidence: 99%
“…9 At our clinics, women are counselled about the common side-effects and complications of the COC pill. This prevents them from panicking when minor side-effects occur.…”
Section: Discussionmentioning
confidence: 99%
“…Answers are then often grouped into large ambiguous categories such as 'health concerns' or 'opposition to use' making it difficult to understand the nuances behind the reasons [14]. There have been several qualitative studies on attitudes towards contraceptive use that cite health concerns as a barrier to contraceptive use and continuation [15][16][17][18], but, similarly to DHS data, the distinction between unsubstantiated fears and the experience of side effects is not systematically articulated. This is problematic because it leads to the assumption that concerns about side-effects are grounded in myths and misconceptions that can be alleviated by counselling and education [5,8,9], disregarding the possibility that side-effects may be intolerable [19].…”
Section: The Reasons For Contraceptive Discontinuationmentioning
confidence: 99%
“…Estudos mostraram que, quando o relacionamento se torna mais estável, os casais tendem a trocar o preservativo masculino por um MAC hormonal, uma vez que se estabelece uma confiança maior entre o casal, e a preocupação com as ITS diminui (Bastos et al, 2008;Beltzer et al, 2011;D'Antona et al, 2009;Shih et al, 2011;Goldstein, Upadhyay, Raine, 2013;Mehra et al, 2014). Na França, as usuárias do preservativo masculino interromperam o uso ou trocaram de MAC assim que o relacionamento tornou-se estável (Beltzer et al, 2011).…”
Section: Descontinuidades No Uso Do Preservativo Masculino E Fatores unclassified
“…No estudo de Gibbs et al (2014), quanto maior a idade, maior a inconsistência no uso do preservativo masculino, o que pode estar interligado com o tipo de relacionamento, já que é mais provável que as mulheres mais velhas estejam em uma união estável do que as mais jovens. Entre as mulheres deste estudo, uma maior proporção de mulheres casadas encontrava-se na faixa etária de 25 a 34 anos de idade (43,7%) em comparação com as de 18 a 24 anos de idade (24,7%) (dado não apresentado), e a estabilidade no relacionamento é elemento importante para descontinuar o uso do preservativo masculino (Bastos et al, 2008;D'Antona et al, 2009;Shih et al, 2011;Goldstein, Upadhyay, Raine, 2013;Mehra et al, 2014;Beltzer et al, 2011). Cabe ressaltar que isso pode estar somado às relações de gênero menos igualitárias, que também influenciam na negociação para usar o preservativo masculino (Gibbs et al, 2014;Mehra et al, 2014).…”
Section: Descontinuidades No Uso Do Preservativo Masculino E Fatores unclassified